Denotations of Memory: A Familial Archive - Williams, Joshua (2019)
Denotations of Memory: A Familial Archive is an evocative exploration of memory centred on a familial archive. Notions of memory as well the memories themselves in the archive are explored in the form of paintings, sculptures, photographs, installation and videos. A major part of this work focuses on living in Cape Town, South Africa, which was the central location of my lived reality while I was reflecting on the past as embodied in the familial archive.